GOING GLOBAL: GLOBAL MARKETING, SOCIAL AND CULTURAL ENVIRONMENTS IN TRANSITIONAL ECONOMIES - Faruk Ahmeti (European Scientific Journal, ESJ, 2015)
The era of change has reached also countries in every corner of Europe, which until now were closed and have had a centralized economy. The best example is countries in South Eastern Europe (SEE), in particular countries emerged from ex-Yugoslavia, which are going through the transition process for many years. Like many developed countries that have changed the way of operating, developing and in transition countries are trying to switch from one economy to another, from closed and centralized to open and a free market economy. As the market is becoming more open for new entries, highly decentralized organizations are operating across a broad range of countries, without tending to centralize their operation to a single location. Hence, this has minimized the importance of a geographic area (as well as the home region) and is no longer treated as a priori to be the primary base for any (or all) functional area of global organizations. Many functions that are part of every organization, such as sourcing, manufacturing, marketing and sales is performed in the location(s) around the world, which are seen as most suitable for that particular function to be carried. All those changes, even many other that are seen that will happen in the near future, has been realized thanks to technology improvement and globalization that shaped the world. As the technology supports to govern human preferences; globalization has its impact on economic realities.